Comparison of Cardiac Computed Tomography With Transesophageal Echocardiography for Identifying Vegetation and Intracardiac Complications in Patients With Infective Endocarditis in the Era of 3-Dimensional Images. (March 2018) - Kim, In-Cheol; Chang, Suyon; Hong, Geu-Ru; Lee, Seung Hyun; Lee, Sak; Ha, Jong-Won; Chang, Byung-Chul; Kim, Young Jin; Shim, Chi Young
Abstract : Background—: Recent evolution of cardiac computed tomography (CT) provides useful information about valvular and perivalvular structures. We compared the diagnostic performance of CT and transesophageal echocardiography (TEE) with applications of 3-dimensional reconstruction in detecting vegetation and intracardiac complications in patients with infective endocarditis (IE). Methods and Results—: Seventy-five patients (53 men; age, 58±15 years) with definite IE who underwent TEE and CT with 3-dimensional reconstruction within 3 days were analyzed. The diagnostic performances of the 2 modalities for vegetation and IE-related intracardiac complications (valve perforation, valve aneurysm, perivalvular abscess, pseudoaneurysm, fistula, and prosthetic valve dehiscence) were compared. The detection rate of vegetation in TEE and CT was 97.3% and 72.0%, respectively. The maximum sizes of vegetation identified by TEE and CT were well correlated ( r =0.593; P <0.001), especially in patients with large vegetation (≥10 mm), suggestive of a high risk of systemic embolism ( r =0.608; P <0.001). However, small vegetation (<10 mm) was underdiagnosed by CT (52.8%) compared with TEE (94.4%), and the sizes of the 2 modalities were poorly correlated ( r =0.187; P =0.445). Both modalities showed fair diagnostic performance for detecting IE-related intracardiac complications with excellent agreement. TEE was more useful for diagnosing valve perforation and intracardiac fistula, whereas CT was better for diagnosing perivalvular abscess. Conclusions—: Cardiac CT shows a comparable diagnostic performance with TEE for large vegetation and several IE-related complications. TEE is better for detecting small vegetation, valve perforation, and intracardiac fistula, whereas CT is more useful for detecting perivalvular abscess and coronary artery disease.